Aligning teaching with current experiences of being, becoming and belonging: An identity perspective on the use of digital resources - Charlotte Krog Skott; Giorgos Psycharis; Jeppe Skott (Mathematics Education in the Digital Age: Learning Practice and Theory., 2021)
The chapter is on how social issues influence teachers’ use of digital resources in mathematics classrooms. The study is on an experienced, digitally competent, Danish teacher, Sofia, and one question is how her use of digital resources relates to her shifting professional identities. To address the question, a framework called Patterns of Participation, PoP, is used, one that draws on the notions of practice and figured worlds from social practice theory and of self and interaction from symbolic interactionism. Another question is whether PoP is helpful for understanding how Sofia contributes to classroom interaction when using digital resources. Sofia’s case was previously analysed with another framework, Structuring Features of Classroom Practice, which is developed to study teachers’ expertise and development in relation to digital resources. The PoP perspective supplements the previous and primarily descriptive account by providing explanations for how digital resources are used in Sofia’s classrooms, including a focus on procedures and a paucity of attention to conceptual understanding and mathematical reasoning. These explanations relate to Sofia’s identities, understood as her professional experiences of being, becoming and belonging. The PoP analysis, then, offers contextual interpretations and explanations of teachers' acts as related to broader social enterprises beyond classroom interactions.